The Effect of Corporate Governance on Firm Performance, Evidence from Egypt - Emile, Rimon; Ragab, Aiman; Kyaw, Sandy (Asian Economic and Financial Review, 2014)
Corporate governance is well thought-out to have major implications for the growth prediction of an economy. Fine corporate governance practices are viewed as important in decreasing risk for investors; catch the attention of investment capital and improving the performance of firms. However, the way in which corporate governance is prearranged differs between countries, relying on their economic, political and social circumstance.